Design and simulation of die and punch for sheet metal on round bending - Teh, Soon Chiang (2007)
The deflection between FEA simulation and experiment test results still exist which affects the quality and accuracy of the results. Addressing it has become more challenging due to more stringent demands on simulation processes. It is becoming necessary to very rapidly identify sources of unnatural deflection for diagnostic and intervention purposes. The problem include the less efficient design for die and punch, limited die and punch for complex shape, and the unknown displacement control for round shape bending process of sheet metal. For methodology, a v-shape bend experiment and a v-shape bend simulation is done to show result. Comparison between the results of experiment and simulation to measure Algor's analysis accuracy which is applied to simulate round shape bend of sheet metal. Characteristics of sheet metal such as springback are observed during the simulation analysis. In addition, several designs are proposed for round shape bend and to determine which design is best for bending 62.5 mm radius sheet metal. A data sheet containing the displacement control of the press brake machine is developed from the simulation. The framework used to develop the data sheet is general enough for further investigation by either evaluating other designs of its components or by extending its application to other problems.